Carpentry Apprentice Related Training. Instructor's Manual. First, Second, Third, Fourth Years of a Four-Year Series in Four Volumes. - Washington State Coordinating Council for Occupational Education, Olympia; Washington State Coordinating Council for Occupational Education, Olympia ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
The course of related study in the carpentry trade is designed to meet the need for organized study in the various technical aspects necessary for an apprentice to become a well-trained journeyman. Divided into four one-year programs, the instructor's manual for the first year presents lessons on familiarizing the student with the trade and its related aspects, and lessons on tools, materials, scaffolds and staging, basic blueprint and plot layout, and foundations and slabs. Topics covered in the second year are rough framing, roof framing, and stair construction. Third year topics are exterior covering, trim, and insulation; interior finish; timber structures; and concrete construction. Blueprints, the basic principles of estimating and instrumentation, and an analysis and review of all four years of related instruction compose the elements of the program's fourth year. The lessons in the second, third, and fourth volumes are preceded by an up-dating of information on worker-related legislation, both at the State and at the Federal level. Each lesson outline includes lesson objectives, references, visual aids, study assignments, important study points, work assignments, an introduction to the next lesson, and a material list for the next lesson. (AG)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Apprenticeships; Building Trades; Carpentry; Course Content; Course Objectives; Course Organization; Courses; Federal Legislation; Labor Legislation; State Legislation; Teaching Guides; Trade and Industrial Education; Washington